A phase I study to evaluate the safety, tolerability, and pharmacokinetics of a novel, potent GABA analog HSK16149 in healthy Chinese subjects - Chen, Qian; Wu, Qingqing; Song, Rong; Wang, Yating; Zhang, Mengqi; Li, Fangqiong; Zeng, Weifang; Wang, Wei; Jia, Jingying; Yu, Chen; Liu, Yanmei (Frontiers in Pharmacology, 2023)
Purpose: HSK16149 is a novel, potent gamma-aminobutyric acid (GABA) analog for the treatment of neuropathic pain. This study aimed to evaluate the safety, tolerability, and pharmacokinetics of HSK16149 after single and multiple doses in healthy Chinese subjects. Methods: The randomized, double-blind, placebo-controlled study comprised two parts: SAD (single ascending-dose study) and MAD (multiple ascending-dose study). A total of 122 healthy subjects were enrolled in this study. HSK16149 capsule or placebo was administered as the protocol required. The safety of the drug was evaluated through clinical examinations and adverse events. Blood and urine samples were collected at the designated time intervals for pharmacokinetic analysis. Results: Subjects were generally well tolerated after HSK16149 administration and the most common treatment-emergent adverse event (TEAEs) was dizziness, which was expected based on the mechanism of action of HSK16149. In SAD, AUC and Cmax were shown to have a dose-proportional relationship in the dose range of 5-120 mg. The t1/2 of HSK16149 is 3.7-6.4 h. In MAD, after a single and multiple administration of 15-80 mg, AUC and Cmax are proportional to the increased dose of HSK16149, and the accumulative ratios of AUC and Cmax at steady-state were 1.05–1.44 and 1.07–1.36, respectively, indicating that HSK16149 only accumulated slightly after repeated administration. Conclusion: HSK16149 was well tolerated in healthy Chinese subjects. Based on the safety and pharmacokinetic data, 80 mg twice daily (BID) was suggested as the highest target dose for further clinical development. Clinical Trial Registration:http://www.chinadrugtrials.org.cn, identifier CTR20182535 and CTR20191317